Prognostic Value of B7-H3 and a Novel Scoring System in Localized Renal Cell Carcinoma - Faruk Recep Özalp; Kutsal Yörükoğlu; Eda Çalışkan Yıldırım; Mehmet Uzun; Erkut Demirciler; Hüseyin Salih Semiz (Medicina)
Background and Objectives: Renal cell carcinoma (RCC) is a biologically heterogeneous malignancy, and traditional prognostic models often fail to provide accurate risk stratification. B7-H3 (CD276), an immune checkpoint molecule, has been implicated in RCC progression but remains underexplored as a prognostic biomarker. Materials and Methods: This retrospective study analyzed 52 patients with localized RCC who underwent nephrectomy. Immunohistochemical staining was used to assess B7-H3 expression. A novel prognostic scoring system, the Renal Immune Prognostic Index (RIPI), incorporating B7-H3 expression, tumor necrosis, tumor grade, and pathological staging, was developed and validated. Kaplan–Meier survival analysis and Cox proportional hazard models were employed to evaluate disease-free survival (DFS) and overall survival (OS). Results: High B7-H3 expression was significantly associated with shorter DFS (12 vs. 54 months; p = 0.001) and OS (70 vs. 123 months; p = 0.002). The RIPI demonstrated strong prognostic performance, stratifying the patients into distinct risk groups with a C-index of 0.82. The high-risk patients had a median DFS of 14 months, compared with 125 months in the low-risk group (p < 0.001). Conclusions: B7-H3 expression serves as a significant prognostic biomarker in localized RCC, correlating with poorer survival outcomes. The integration of B7-H3 into the RIPI enhances risk stratification by incorporating both molecular and pathological features. These findings support the incorporation of immune biomarkers into clinical practice and highlight B7-H3 as a potential target for novel therapeutic strategies in RCC.